2020
DOI: 10.1002/fsn3.1648
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Toxoplasma activity and chemical compositions of aquatic extract of Mentha pulegium L. and Rubus idaeus L.: An in vitro study

Abstract: This study aimed to determine the chemical compositions of crude aquatic extracts of M. pulegium L. and R. idaeus L., and their anti‐ Toxoplasma activity. Crude aquatic extraction of aerial parts of R. idaeus L. and M. pulegium L. was performed. GC‐MS and HTPLC analyses were carried out. MTT assay was performed on Vero cells treated by different concentrations (Log −10 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…T. gondii is an opportunistic and life-threatening parasite, particularly in AIDS patients, cancer patients, and organ transplant recipients [ 3 , 7 ]; therefore, treatment of human toxoplasmosis seems to be an urgent need for susceptible groups. Several studies have evaluated the effects of herbal medicines on T. gondii [ 10 , 36 , 53 56 ]. A. indica (Neem) belongs to Mahogany family and has been used as herbal medicine, particularly in Africa and south of Asia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…T. gondii is an opportunistic and life-threatening parasite, particularly in AIDS patients, cancer patients, and organ transplant recipients [ 3 , 7 ]; therefore, treatment of human toxoplasmosis seems to be an urgent need for susceptible groups. Several studies have evaluated the effects of herbal medicines on T. gondii [ 10 , 36 , 53 56 ]. A. indica (Neem) belongs to Mahogany family and has been used as herbal medicine, particularly in Africa and south of Asia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, unspecific standard dosage, low stability, unknown side effects, low bioavailability, and low available scientific evidence seem to be the main concerns for the commercial development of the herbal medicine [ 61 ]. For example, Mohammad Rahimi et al [ 36 ] showed that although the aqueous extract of Mentha pulegium L. and Rubus idaeus L. presented promising anti- Toxoplasma effects, cell toxicity of the extracts, particularly, R. idaeus L. limited employing of R. idaeus L. for herbal therapy. The nanoformulation of the herbal extracts can not only increase the bioavailability, effectiveness, and target delivery, but also decrease the aforementioned limitations of the herbal extracts [ 9 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations